2009
DOI: 10.1080/09720073.2009.11891112
|View full text |Cite
|
Sign up to set email alerts
|

Age at Natural Menopause among Rural and Urban Punjabi Brahmin Females

Abstract: Present study is an attempt to estimate age at natural menopause among rural and urban Punjabi Brahmin females of Roop Nagar district (Punjab). Cross-sectional data are based on 870 Brahmin females (rural=450, urban=420), ranging in age from 40 to 70 years. Mean and median age at menopause of rural females is 48.22+2.47 years and 48.98+1.12 years respectively, while among urban females it is 49.30+2.80 years and 50.12+1.15 years, respectively. These findings indicate that urban Brahmin females experience menop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
2
10
0
1
Order By: Relevance
“…The mean age at menopause among the postmenopausal women was 49.9 which similar to the mean age at menopause for Indian women. [ 15 16 ] Dietary practices and physical activity levels have a potential to affects a person's quality of life. Studies focussing on current dietary intake among Indian postmenopausal women are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age at menopause among the postmenopausal women was 49.9 which similar to the mean age at menopause for Indian women. [ 15 16 ] Dietary practices and physical activity levels have a potential to affects a person's quality of life. Studies focussing on current dietary intake among Indian postmenopausal women are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The natural menopause can vary greatly between individuals and on average, occurs naturally at the age of 51 years in industrial countries and is 48 years in poor and non-industrialized countries 234. The timing of menopause is a known risk factor for several chronic diseases like coronary heart disease, osteoporosis and cancers.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The natural menopause can vary greatly between individuals and on average, occurs naturally at the age of 51 years in industrial countries and is 48 years in poor and non-industrialized countries. 2 3 4 The timing of menopause is a known risk factor for several chronic diseases like coronary heart disease, osteoporosis and cancers. Some studies reported that early menopause is associated with increased mortality from cardiovascular diseases, 5 6 7 8 and older age at menopause increases the risk of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The mean age at natural menopause (ANM) is 51 years in industrialized nations, while it is 48 years in poor and non-industrialized nations. [ 1 2 3 ] Menopause is not a central event but rather a result of primary ovarian failure secondary to apoptosis or programmed cell death. This results in reduced production of estradiol, the most active form of estrogen as well as increased levels of follicle-stimulating hormone (FSH) and decreased levels of inhibin.…”
Section: Introductionmentioning
confidence: 99%